Hereditary chin trembling - Işıkay, Şedat (Wolters Kluwer Medknow Publications)
[No abstract available]

[No abstract available]
Keywords: botulinum toxin; botulinum toxin; case report; case report; child; child; chin; chin; chinclinical article; chinclinical article